An oral pharyngeal scope for objective oropharyngeal examination: a new device for oropharyngeal study. - Koichi Tsunoda; Rika Kobayashi; Akiko Kada; Akiko M. Saito; Fumiyuki Goto; Yoichiro Sugiyama; Yasuo Hisa; Kenji Kondo; Atsunobu Tsunoda; Keizo Horibe; Hayato Misawa; Toru Sasaki; et al. (Acta Oto-Laryngologica (Supplement), 2018)
Objective: There has been little progress in examination of the oropharynx with a light source such as electric light, a penlight, or a forehead mirror over the past 100 years. It is therefore necessary to develop methods to display and record oropharyngeal observations. Method: Since the aim of this study was to assess the safeness to use from the perspective of physicians, medical staffs, patients, and patients' families and usefulness of pharyngeal scope, the number of devices was limited, the number of patients was not set based on hypothetical statistical tests. Results: A total of 150 volunteers were enrolled in this study. Among them, 96 underwent examination alone and the remaining 28 underwent treatment procedures. The study was done without any complications in all 150 cases. Most (91.3%) physicians hoped to continue using the new device if available. When comparing the use of the device for observation alone and for treatment procedures, there was no significant difference for evaluation items (p > .05) except convenience factor which received a significantly different (p = .0154) evaluation from physicians for observation alone and for treatment procedures. A positive evaluation was received about examination, recording/display and explanation from the patients and patients' families. Conclusions: Our new device received positive evaluations by who underwent examination of the oral cavity and pharynx, recording of the results, and treatment procedures.